Characterization of occult hepatitis B infection among Iranian liver transplant recipients. Issue 10 (9th September 2022) - Khamseh, Azam; Poortahmasebi, Vahdat; Soltani, Saber; Nasiritoosi, Mohsen; Jafarian, Ali; Ghaziasadi, Azam; Norouzi, Mehdi; Ghorbani, Saied; Eslami, Narges; Jazayeri, Seyed Mohammad
Abstract: Background: The prevalence of occult hepatitis B infection (OBI) among Iranian liver transplant recipient patients has not been explored yet. The present study aimed to determine the OBI prevalence among Iranian liver transplant recipients. Methods: This study encompassed 97 patients having undergone liver transplantation due to several clinical backgrounds in the Liver Transplantation Center, Tehran, Iran. After serological evaluation, two different types of PCR methods were applied for amplification of HBV DNA, followed by the direct sequencing of whole hepatitis B virus (HBV) surface genes. Results: At the time of admission, none of the patients were positive for HBsAg. However, 24 (25%), 12 (12.3%), and 5 (5.1%) cases were positive for anti‐HBc, hepatitis C virus (HCV), and hepatitis delta virus (HDV) antibodies, respectively. Moreover, two males were positive for OBI (2.1%). Both were positive for anti‐HBc and negative for anti‐HBs, anti‐HCV, and anti‐HDV. HBV‐related cirrhosis was the underlying reason for their liver transplantation. HBsAg sequences revealed no amino acid substitution. Conclusions: The prevalence of OBI in the Iranian liver transplantation patients was relatively low. Future longitudinal studies with a larger sample size are suggested to explore the significance of this clinical finding, including the reactivation of cryptic HBV DNA, in liver transplant subjects. Abstract : The aim of this study was to characterize the prevalence of occult HBV infection in a series of liver transplant recipients. The present study comprised 97 patients who underwent liver transplantation. HBV serologic and molecular assays were performed. The hepatitis B surface antigen (HBsAg) genes from HBV‐DNA‐positive samples were amplified and directly sequenced. At the time of presentation, none were positive for HBsAg. However, 24 (25%), 12 (12.3%), and 5 (5.1%) were positive for anti‐HBc, hepatitis C virus (HCV), and hepatitis delta virus (HDV) antibodies, respectively. Two males were positive for OBI (2.1%). Both were positive for anti‐HBc and were negative for anti‐HBs, anti‐HCV, and anti‐HDV. HBV‐related cirrhosis was the underlying reason for their liver transplantation. Both OBI samples belonged to HBV genotype D and subtype awy2. HBsAg sequences did not show any amino acid substitution.